Governance quality and sustainability: Uncovering the moderating role of commitment and assessment - Satyaguna, I Made; Riyadi, Slamet; Halik, Abdul (Edelweiss Applied Science and Technology, 2024)
Corporate governance reform in Indonesia after the Asian financial crisis and global scandals shows a lag in effectiveness, with the lowest governance rating of 33.6 in 2020. Despite regulatory improvements, weak leadership commitment and failure of governance implementation hinder improvements. In-depth evaluation and reform are needed for significant improvement. Governance quality and commitment are important for sustainability, but the study has limitations. This, raises violations in governance and sustainability, which requires further exploration of external variables and factors. This study integrates RBV to understand the effect of governance assessment and quality on corporate sustainability on the Indonesia Stock Exchange. This study assesses the effect of Commitment (M1) and Governance Quality (X) on Sustainability (Y) to show significant results. This study explanatory uses a survey with a Likert Scale to evaluate commitment, governance, and sustainability involving management with a higher education background, using a questionnaire distributed via email and WhatsApp. This study uses the SEM-PLS procedure with SmartPLS 3.2.9 to test the relationship between variables and construct validity, as well as model evaluation. This study shows that Commitment (M1) and Governance Quality (X) have a significant influence on Sustainability (Y), with T Statistics of 6.494 and 3.431, and p-values of 0.000 and 0.001. In contrast, Assessment (M2) has no significant influence, with T Statistics below 1.96 and p-value greater than 0.05. The blindfolding analysis model shows a Q² for Sustainability (Y) of 0.539, with R² of 0.756 and R² Adjusted of 0.744. Future research should explore additional factors or different methodologies to deepen understanding.